Thermoregulation during marathon running - Faude, O.; Donath, L. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
Marathon running is a popular psycho-physiologically demanding endurance event. As the majority of the energy produced during a marathon is converted to heat, marathon running is considered a particular challenge for the thermoregulatory system. Marathon race pace is mainly determined by the oxygen uptake (V02) which can be maintained during the run and running economy. Marathons are ran at an exercise intensity ranging from 60 to 85 % of maximal oxygen uptake, depending on the performance level of the athlete. The main factors affecting thermoregulation are environmental conditions and dehydration. Changes in body temperature during long-distance endurance events are the result of heat production and heat loss. Premature hyperthermia negatively affects the cardiovascular, central nervous and muscular systems. Excess heat can be dissipated by radiation, conduction, convection and evaporation. Radiation (~60 %) and convection (~ 15 %) make up the greatest part of heat loss at rest. The proportion of heat loss by evaporation rises during exercise and is the main source for heat dissipation in warm environmental conditions. The two main physiological mechanisms for heat loss are an increase in skin blood flow and sweating. Potential strategies to counter health risks and performance decrements when performing in extreme environments are heat acclimation, appropriate hydration, precooling and adequate clothing.